2001
DOI: 10.4049/jimmunol.167.8.4765
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Induces Allergic Sensitization in Mice

Abstract: Epidemiological studies have suggested increased prevalence of atopy in children of maternal smokers. Although secondhand smoke or environmental tobacco smoke (ETS) has been shown to augment allergic responses, its role in atopic sensitization is still controversial. We studied whether ETS could initiate a Th2 response and thus induce primary allergic sensitization. Mice were exposed for 10 consecutive days to either 1% aerosolized OVA, ETS (5 cigarettes), or both ETS and OVA. C57BL/6 mice receiving both ETS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 33 publications
0
53
1
Order By: Relevance
“…The increased numbers of peribronchial eosinophils in mice exposed to chronic ETS and chronic OVA was associated with a trend to increased levels of eosinophil active cytokines and chemokines such as IL-5 and eotaxin-1. Increased expression of Th2 cytokines such as IL-5 have previously been noted in studies of mice exposed to ETS and acute OVA allergen (17,18). Increased expression of eotaxin-1 in mice coexposed to ETS and OVA has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…The increased numbers of peribronchial eosinophils in mice exposed to chronic ETS and chronic OVA was associated with a trend to increased levels of eosinophil active cytokines and chemokines such as IL-5 and eotaxin-1. Increased expression of Th2 cytokines such as IL-5 have previously been noted in studies of mice exposed to ETS and acute OVA allergen (17,18). Increased expression of eotaxin-1 in mice coexposed to ETS and OVA has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, SHS exposure has an adjuvant effect, characterized by an increase in antigen-specific IgE, elevated Th2 responses, and influx of eosinophils into the lungs (7,8). It is unclear which of the more than 6,000 compounds in sidestream tobacco smoke act as adjuvants; however, other particulate pollutants resulting from incomplete combustion of organic materials, such as ambient particulate matter and diesel exhaust, contain many of the constituents of SHS, such as polyaromatic hydrocarbons, suggesting that a spectrum of xenobiotics in the environment can contribute to enhancement of responses to allergens (9,17,(39)(40)(41).…”
Section: Table 5 Correlation Of Differences In Nasal Allergic Endpoimentioning
confidence: 99%
“…The explanation for the heightened sensitivity among those with allergic airway diseases is likely multifactorial, but involves synergistic effects of SHS and allergens in initiating and exacerbating allergic airway diseases (6)(7)(8). In conjunction with allergen, SHS can act to enhance IgE antibody responses, T-helper cell (Th) 2 cytokine production, and histamine release in vivo (6).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…We (Seymour et al, 1998) and others (McMenamin et al, 1994) have shown that repeated exposure of naive adult mice to aerosolized OVA resulted in IgE unresponsiveness. However Rumold et al (2001) have demonstrated that exposure of naïve adult mice to aerosolized OVA along with ETS resulted in elevated levels of serum IgE and eosinophils in the BAL. These observations prompted an interest in further investigating the effects of ETS on exposure to a clinically relevant and more complex antigen.…”
Section: Introductionmentioning
confidence: 99%